Chromatin Modifiers in Transcriptional Regulation: New Findings and Prospects - Mazina, M. Yu. (Acta Naturae, 2021)
Histone-modifying and remodeling complexes are considered the main coregulators that affect transcription by changing the chromatin structure. Coordinated action by these complexes is essential for the transcriptional activation of any eukaryotic gene. In this review, we discuss current trends in the study of histone modifiers and chromatin remodelers, including the functional impact of transcriptional proteins/ complexes i.e., “pioneers”; remodeling and modification of non-histone proteins by transcriptional complexes; the supplementary functions of the non-catalytic subunits of remodelers, and the participation of histone modifiers in the “pause” of RNA polymerase II. The review also includes a scheme illustrating the mechanisms of recruitment of the main classes of remodelers and chromatin modifiers to various sites in the genome and their functional activities.